An efficient organic/inorganic phosphorus–nitrogen–silicon flame retardant towards low-flammability epoxy resin - Luo, Haiqiang; Rao, Wenhui; Zhao, Peng; Wang, Liang; Liu, Yuanli; Yu, Chuanbai (Polymer degradation and stability, 2020)
In this paper, an organic/inorganic phosphorus–nitrogen–silicon flame retardant (DPHK) was synthesized by Kabachnik-Fields reaction and the sol-gel method, then it was used as a reactive flame retardant to prepare flame-retardant and smoke-suppressant epoxy resins (EP). The influence of DPHK on the flame retardancy of EP was investigated by limiting oxygen index (LOI), vertical burning test (UL-94 V) and cone calorimeter (CC) test. The results revealed that the EP containing only 3 wt% DPHK achieved UL-94 V-0 rating, and the corresponding LOI value reached 29%. Furthermore, the cone calorimeter results demonstrated that the DPHK effectively reduced the heat release rate (HRR) and total release rate (THR) of the EP. Compared with EP, the peak of heat release rate (PHRR) and THR of 4%DPHK-EP reduced by 36% and 30%, respectively. More importantly, the incorporation of DPHK suppressed the release of toxic fuel (CO) and smoke of EP, meanwhile, the increased char residue and CO/CO2 ratio of the DPHK-EP samples proved that DPHK presented not only the condensed-phase activity but also gas-phase activity. Furthermore, the involved gases and char residues were studied by using thermogravimetric analysis coupled with coupled with Fourier transform infrared spectrometry (TG-FTIR), pyrolysis gas chromatography/mass spectrometry (Py-GC/MS), scanning electronic microscope together with the energy dispersive X-ray spectrometer (SEM-EDX) and X-ray photoelectron spectroscopy (XPS). The results certified the charring effect of the phosphaphenanthrene group and the enhancing effect of the silicon group. Subsequently, the flame inhibition effect and lesser combustible gases release enhanced the flame-retardant properties of EP. •An organic/inorganic phosphorus–nitrogen–silicon flame retardant was designed and synthesized.•The DPHK show high flame-retardant efficiency in epoxy thermosets.•The DPHK exhibit gas-condensed bi-phase flame-retardant action.